PROTECTION IN CONSUMER RELATIONS ARISING FROM THE USE OF DISRUPTIVE TECHNOLOGIES IN VIRTUAL CURRENCIES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2012)
In this work, an exploratory study is made about the technology of virtual currencies and their impact on consumer relations. The methodology used is based on the verification of the laws and doctrines relevant to the subject, as well as on literature from different sciences because it is an interdisciplinary issue related to Information Technology. The approach is qualitative, supported by literature review and descriptive analysis of the researched phenomena, in addition to consultation on the legislation on the subject. The contribution is relevant due and importance of the topic in the financial and legal context of transactions carried out in virtual mode. It is concluded that the emergence of disruptive digital technologies such as cryptocurrencies are revamping financial services and access infrastructures pose new challenges and opportunities for consumers and regulators.